The foundation of Belo Horizonte: order, progress and hygiene, but not for all - Fernandes, Patrícia Capanema Alvares (Cadernos Metrópole, 2021)
The plan for Belo Horizonte, founded at the turn of the 19th century, was premised by order, progress and hygiene. The city has displayed, however, a peculiar pattern of social-spatial exclusion since its beginnings. This pattern has be traced back to the plan, as it foresaw the construction of an elitist urban area in replacement of the existing village, evicting former residents and poor newcomers and relegating them to the unorganized, unhygienic suburbs as well as to at-risk and environmentally fragile areas. This historiographic research reveals which mechanisms and practices led to such socialspatial segregation, working outside and as a result of its plan, while challenging simplistic “rich-center/poor-periphery” dichotomies that have dominated Belo Horizonte’s historiography, unveiling instead a much more complex reality.